116PClinical significance and converionrate relevance of RAS genetic mutation analysis for unresectable colorectal liver metastases: A single-center retrospective study. (24th November 2019) - Ji, M; Tang, W
Abstract: Background: RAS mutation has become an important part of assessment of patients with colorectal cancer (CRC), but its role in colorectal cancer patients with initially unresectable liver metastases has yet to be elaborated. We aim to assess the role of RAS mutation on convertion of patients with initially unresectable colorectal liver metastases (CLMs). Methods: We identified CRC patients who initially with unresectable liver metastases during January 2012 to December 2017 in Zhongshan Hospital Fudan University. The association between RAS status of primary tumor and characteristics of patients were analyzed. Conversion rates was determined. Results: A total of consecutive 433 CLM patients with available RAS status were evaluated in this study, KRAS mutation rates was 41.5%, BRAF was 6.7% and NRAS was 1.6%. 258 patients were RAS wild type and 185 patients were mutant. RAS mutation were associated with right colon cancer (P = 0.006) and lymph node metastasis (P = 0.017). Among RAS wild type patients, 56.2% (145/258) received Cetuximab plus chemotherapy treatment, 7.8% (20/258) received Bevacizumab plus chemotherapy and the others received chemotherapy only. Among RAS mutant patients, 50.8% (94/185) received Bevacizumab plus chemotherapy and 49.2% (91/185) received chemotherapy only. RAS wild type patients had a better objective response rate (52.3% vs 37.3%, p = 0.011) and higher conversion rate (24.0% vs 12.4%, P = 0.002) compare with RAS mutant patients. For RAS wild type group, patients with Cetuximab plus chemotherapy, Bevacizumab plus chemotherapy and chemotherapy only have a conversion resection rate of 31.5%, 20% and 14.3% respectively P = 0.05 for RAS mutation group, Bevacizumab plus chemotherapy had a similar conversion resection rate compared with chemotherapy only (12.6% VS 11.3%, P = 0.815). Conclusions: RAS wild type indicated a better conversion rate for patients with initially unresectable colorectal liver metastases. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.